Four attachment-based categories of emotion regulation in adolescent psychic troubles - Robin, Marion; Surjous, Luc; Belbèze, Jean; Bonnardel, Lucile; Lamas, Claire; Silva, Jérôme; Peres, Victoire; Corcos, Maurice (Frontiers in Psychology, 2023)
Emotion regulation is altered in many psychiatric disorders in adolescence, but the understanding of mechanisms that underlie this alteration is still poor. The PERCEPT study explores alexithymia, empathy, facial emotion recognition (FER) and defense mechanisms in a sample of adolescents in psychiatric care (n=61 patients, 45 girls, mean age=15.03 y.o., including 36.1% of anxiety or depressive disorder, 39.3% of Borderline Personality Disorder, 32.8% of Eating Disorders, and 22.9% of psychosis), in relation with participants’ attachment styles. Results revealed correlations between attachment dimensions and all of the emotion regulation variables, suggesting that attachment modalities have functional links with emotional regulation at its different levels: FER accuracy was inversely correlated with avoidant attachment, while affective empathy, difficulty in identifying feelings (alexithymia) and immature as well as neurotic defense mechanisms were positively correlated with anxious attachment. Moreover, attachment categories delineated distinct emotional perception profiles. In particular, preoccupied attachment included adolescents with the highest levels of facial emotion perception (sensitivity and accuracy) and of affective empathy, whereas detached attachment included adolescents with the lowest levels of these variables. Neurotic defense mechanisms and difficulty to identify feelings were correlated with preoccupied attachment; immature defense mechanisms and difficulty to describe feelings to others characterized fearful attachment. These results suggest that attachment categories underlie emotion regulation processes in psychiatric disorders in adolescence. Theoretical and clinical implications are discussed.